DETERMINANTS OF PROFITABILITY OF ISLAMIC COMMERCIAL BANKS (BUS): AN EMPIRICAL STUDY OF THE EFFECT OF FDR, CAR, AND NPF IN THE 2020-2024 PERIOD - Heru Setyowiyono; Restu Asa Marisza Sukma; Gayuh Kawedar; Rohmad Subagyo; Mohammad Aswad (Journal of Economic, Bussines and Accounting (COSTING), 2025)
The growth of Islamic banking assets in Indonesia during 2020–2024 does not align with profitability, which has shown volatility. This phenomenon indicates the need for a reassessment of the determinants of profitability in the post-pandemic period. Within the context of restructuring policies, this study evaluates the determinants of profitability (ROA) of Islamic Commercial Banks. A quantitative-associative analysis was applied using a multiple linear regression model based on secondary financial report data to examine the roles of the Financing to Deposit Ratio, Capital Adequacy Ratio, and Non-Performing Financing Ratio. The findings reveal results that differ from most previous studies. It was found that FDR has a positive and significant effect, confirming the importance of intermediation activities. Conversely, CAR has a negative and significant effect, indicating potential inefficiency caused by excess capital. Furthermore, NPF was found to have no significant effect, a finding identified as a consequence of financing restructuring policies. These results demonstrate that the determinants of Islamic bank profitability have shifted, where the efficiency of capital management is now a more influential factor compared to credit risk, whose impact has been mitigated by policy interventions.